1984
DOI: 10.1177/1077727x8401300205
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Fashion Awareness and Clothing Economic Practices

Abstract: The Sproles Consumer Interest and Priorities questionnaire was administered to the 3,036 members of Home Economists in Business (HEIB) in order to test the hypotheses that the data would reveal: (1) significant correlations between fashion awareness and clothing economic practices, and (2) identifiable con sumer profiles, concerning economic attitudes and activities, applicable to in dividuals exhibiting either high or low fashion awareness. Positive correlations were observed between fashion awareness respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 7 publications
1
17
0
5
Order By: Relevance
“…Secondly, the study aimed to involve young females because findings from previous research studies indicated that fashion leaders are more likely to be young (Gutman & Mills, 1982;Horridge & Richards, 1984;Goldsmith & Hofacker, 1991;Beaudion et al, 1998) and that they have an affinity for fashion products that allow for the expression of their uniqueness (Parker et al, 2004). Thirdly, based on fashion clothing as the domain for the survey, a decision was made to involve females shopping at Young Designers Emporium (YDE) and RJL in the Menlyn Shopping Centre because these stores offer unique desirability bias (Bearden et al, 1993:59).…”
Section: Research Problem and Objectivesmentioning
confidence: 99%
“…Secondly, the study aimed to involve young females because findings from previous research studies indicated that fashion leaders are more likely to be young (Gutman & Mills, 1982;Horridge & Richards, 1984;Goldsmith & Hofacker, 1991;Beaudion et al, 1998) and that they have an affinity for fashion products that allow for the expression of their uniqueness (Parker et al, 2004). Thirdly, based on fashion clothing as the domain for the survey, a decision was made to involve females shopping at Young Designers Emporium (YDE) and RJL in the Menlyn Shopping Centre because these stores offer unique desirability bias (Bearden et al, 1993:59).…”
Section: Research Problem and Objectivesmentioning
confidence: 99%
“…Specifically, women who read Vogue and Harper's Bazaar were more aware of current fashions than women who read other fashion magazines 24 . Females with high fashion awareness received more pleasure from shopping for clothing, spent more time shopping for clothing, and purchased more clothing on impulse than females with low fashion awareness 25 …”
Section: Introductionmentioning
confidence: 95%
“…They also shop more than other consumers and spend more money on apparel (Goldsmith et al 1991). They buy more apparel on impulse (Horridge and Richards 1984) and read more fashion magazines (Goldsmith et al 1991;Chowdhary 1989). Other studies have also measured fashion involvement (Sproles 1981;Tigert et al 1976) and self-concept (Gutman and Mills 1982) in relation to fashion adoption.…”
Section: Introductionmentioning
confidence: 99%